(untitled) (Research, Society and Development, 2023)
The International Classification of Diseases (ICD) is a universal identifier of diseases and other diseases, through codes, allowing comparability and even communication between different countries about health conditions. In this sense, this study aimed to describe the importance of ICD within the context of HIV mortality in the state of Rondônia, in the period from 2015 to 2020. This is a descriptive study and quantitative approach, conducted a survey of the variables race/color, gender, age group and schooling in the Department of Informatics of the Unified Health System (DataSUS) and analyzed through descriptive statistics in the Microsoft Excel program. It was found that for all chapters of ICD-10, most deaths were male, race/brown color, differentiation in education level and age group between 30 and 59 years. In chapter B-23, indigenous peoples were identified as the relevant group in HIV mortality. In view of the findings found, it was found that the creation of ICD was of great advance for the health area, optimizing the treatment to the patient and of great relevance for health professionals, whose insertion since academic training is essential for the proper conduct and integral management of care.